Square: uma plataforma gráfica e intuitiva para anotação de genomas bacterianos - Eslabão, Marcus Redü (2016)
DNA sequencing is a technique that provides a vast source of information on various organisms. Currently, new sequencing methods known as Next-Generation Sequencing, are making this technique many times more rapid, accurate and affordable, making it popular and widespread in the scientific community. With the popularization of genome sequencing, laboratories that do not have an emphasis on DNA sequencing, are using this approach to complement their studies. However, the ease in obtaining a DNA sequence contrasts with the difficulty to process, analyze and annotate the genome, in order to obtain relevant biological information. To assist researchers who use this technique, several programs are available, however, they are generally not free, do not perform all the necessary analysis or are difficult to use, mainly because a considerable number of them make use of command line to be executed, which is not intuitive. The objective of this study was to create a genome annotation software easy to use, with a user friendly interface, free and able to provide all the necessary information for the annotated genome to be submitted to GenBank. For software implementation named Square, Python and Object Pascal programming languages were used. The Prodigal algorithms, NCBI BLAST and tRNAscan-SE were also integrated in the software. At the end of the development stage, Square was tested with three genomes and compared to two popular annotators: RAST and BASYS. The result showed that the Square has higher accuracy than the other two annotator programs, as the results are similar to what is deposited in NCBI, and produce the result in a shorter time, as it runs locally. The Square proved to be a good alternative for users not familiar with the Linux command terminal and is available in http://sourceforge.net/projects/sqgenome/ address.